The Effect of Methylphenidate on the Hearing of Children with Attention Deficit Hyperactivity Disorder - İsmi,Onur (2018)
Abstract Introduction There has been a sudden idiopathic hearing loss case presented after methylphenidate treatment in a child with attention deficit hyperactivity disorder (ADHD). Objective This study was performed to reveal the probable ototoxic side effects of methylphenidate use in patients with ADHD. Methods Thirty pediatric patients with ADHD were included in the study. Pure tone audiometry, speech discrimination scores, waves I, III, V absolute latencies and waves IIII, I-V, III-V interpeak latencies at the 80 dB nHL intensity after click stimulus auditory brainstem response (ABR) results were compared before and 3 months after methylphenidate treatment. Results There were no statistically significant difference between pretreatment and posttreatment pure tone and speech audiometry findings and ABR results (p > 0.05 for all parameters). Conclusion Methylphenidate can be regarded as a safe drug regarding ototoxic side effects. Additional studies with a larger sample size and longer follow-up may be needed.